Effectiveness of a Learning Potential Procedure in Improving Problem-Solving Skills of Retarded and Nonretarded Children. - Budoff, Milton; Corman, Louise (American Journal of Mental Deficiency, 1976)
The article presents a study to determine the effectiveness of learning potential training on improving problem-solving skills of children on Raven's Coloured Progressive Matrices. Five hundred fifty-three retarded and nonretarded students were pretested randomly assigned to trained or nontrained groups and posttested. The learning potential procedure provided learning experiences related to reasoning skills that might not have been previously obtained in school